LINGUISTIC AND POLITICAL ANALYSIS: COMPARATIVE ASPECTS - V. M. Alpatov (Сравнительная политика, 2015)
Abstract: The article analyses the book on political systems and processes in the East prepared by MGIMO-University authors and edited by Alexei D. Voskressenski in order to show the differences in approach and methods used in linguistics and political science. The author shows two significant differences in present-day stressing that linguistics of the XIX century was closer to the present-day political science? As he believes. The first difference includes monism of political science approach, since the book reveals monistic scale from totalitarianism to democracy, while linguistic has abandoned the monistic view on typology. The second difference is the value-addedness of the political science approach. The value-free norm in linguistics presupposes setting up of a single standard for all speakers in order to reach full mutual understanding. In political science subjective criteria are decisive for evaluation. The article gives examples from the book to prove that political science, compared to linguistics, is not aimed at overcoming contradictions, distinguishing between the terms, avoiding unproved statements and subjective evaluations.